Homeland Security: The Military's Confusing Role - Hershkowitz, Martin (2006)
This article is in the form of an editorial based upon three United States Air Force Air University (AU) "CADRE Quick-Look" articles or "dialogs" by Colonel John L. Conway III (USAF-Retired). Colonel Conway is a military defense analyst assigned to the Air University. "CADRE Quick-Look" serves as a catalyst for air and space power research dialogue. In these "dialogs," Colonel Conway examines the roles of the military and civilian "coalition partners," in particular that of the U.S. Air Force, in meeting the mission requirements of homeland defense (HD) and homeland security (HS). The CADRE Quick-Look dialogs deal with the dual HD and HS roles of NORTHCOM; the competing combat and HD roles of the Air National Guard; and the possible use of the State Defense Force by the Air Force in support of its HS role. All three CADRE Quick-Look dialogues by Colonel Conway are contained herein. See also ADA494463. Published in the State Defense Force Journal, v2 n2, p27-37, Fall 2006. Creative Commons Attribution License. The original document contains color images.